Dynamics of speech etiquette in Russian and Uzbek linguocultures: a comparative analysis of literary discourse - Tillyaeva, Malika Yuldashevna (The Lingua Spectrum, 2026)
The article examines the dynamics of speech etiquette models in Russian and Uzbek literary discourse across different time periods. The material includes works by A.S. Pushkin, M.A. Bulgakov, Yu. Serebryansky, Abdulla Qodiriy, O‘tkir Hoshimov, and Jasur Kengboyev. The comparative analysis focuses on four functional areas of speech etiquette: greeting, address, gratitude, and farewell. The study shows that changes in etiquette models are uneven and cannot be reduced to the successive replacement of older formulas by newer ones. Gratitude demonstrates lexical continuity, whereas greeting and farewell are characterized mainly by functional-register and pragmatic variation. The most significant differences are revealed in forms of address. Russian texts demonstrate different ways of marking interpersonal distance across the selected periods, while Uzbek material shows greater continuity of relational forms based on age, kinship, and social role. The analysis distinguishes three mechanisms of speech etiquette dynamics: lexical continuity, functional-register variation, and structural-relational restructuring, reflecting different levels of transformation while preserving the basic communicative functions of speech etiquette.